2014
DOI: 10.1088/0004-637x/788/1/77
|View full text |Cite|
|
Sign up to set email alerts
|

MILKY WAY RED DWARFS IN THE BoRG SURVEY; GALACTIC SCALE-HEIGHT AND THE DISTRIBUTION OF DWARF STARS IN WFC3 IMAGING

Abstract: We present a tally of Milky Way late-type dwarf stars in 68 Wide Field Camera 3 (WFC3) pure-parallel fields (227 arcmin 2) from the Brightest of Reionizing Galaxies survey for high-redshift galaxies. Using spectroscopically identified M-dwarfs in two public surveys, the Cosmic Assembly Near-IR Deep Extragalactic Legacy Survey and the Early Release Science mosaics, we identify a morphological selection criterion using the half-light radius (r 50), a near-infrared J − H, G − J color region where M-dwarfs are fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 57 publications
(97 reference statements)
2
41
0
Order By: Relevance
“…(iv) If this observed non-uniform substellar distribution remains unchanged after future searches, then either some fortuitous random aggregation or some dynamics affecting primarily the lower mass objects, could be invoked. We note that pencil beam deep surveys of the Milky Way suggests there might be slightly more M-type dwarfs in the Galactic northern hemisphere (b > 0 deg) than in the southern hemisphere (b < 0 deg; see Holwerda et al 2014 and references therein) and hints at a reversal occuring for midto late M-type dwarfs, which would be more numerous in the southern hemisphere. However, as already mentioned in Sect.…”
Section: Discussionmentioning
confidence: 76%
“…(iv) If this observed non-uniform substellar distribution remains unchanged after future searches, then either some fortuitous random aggregation or some dynamics affecting primarily the lower mass objects, could be invoked. We note that pencil beam deep surveys of the Milky Way suggests there might be slightly more M-type dwarfs in the Galactic northern hemisphere (b > 0 deg) than in the southern hemisphere (b < 0 deg; see Holwerda et al 2014 and references therein) and hints at a reversal occuring for midto late M-type dwarfs, which would be more numerous in the southern hemisphere. However, as already mentioned in Sect.…”
Section: Discussionmentioning
confidence: 76%
“…Previous searches for M, L and T-type stars have commonly assumed a single disk model (e.g. Holwerda et al 2014;Ryan et al 2011) to describe the observed number of stars, as the small samples of objects preclude a more complicated analysis. We follow such an approach using a single exponential disk model as described in Caballero et al (2008).…”
Section: Number Density Modelmentioning
confidence: 99%
“…We adopt the main parameters of the galactic thin disk model from Chen et al (2001), with Z = 27 ± 4pc, R = 8600 ± 200pc and hR = 2250 ± 1000 pc. The most relevant quantity for this study is the galactic vertical scale height, where we use two values at hZ = 300 pc and hZ = 400 pc to reflect the uncertainty in this quantity (Holwerda et al 2014;Ryan et al 2011;Pirzkal et al 2009). Fig.…”
Section: Number Density Modelmentioning
confidence: 99%
“…To this aim, we opted for not adopting SExtractor class_star parameter because the classification becomes uncertain at low S/N (e.g., Bertin & Arnouts 1996). To overcome this, other star/galaxy separation criteria based on SExtractor have been developed (see e.g., Holwerda et al 2014). One of the most reliable is the effective radius versus magnitude (Ryan et al 2011).…”
Section: Sample Selectionmentioning
confidence: 99%